Oral health changes in an adult Norwegian population: a cohort analytical approach - Holst D, Schuller AA (Blackwell Synergy, 2000)
The purpose of this analysis was to study temporal variation in oral health in an adult population. The cohort analysis comprised 1) estimation of longitudinal, cross-sectional, and time-lag differences in caries and treatment experience of the adult population in Trøndelag from 1973 to 1983 and to 1994; 2) assessment of which of the effects of age, period and cohort was the most plausible explanation for the observed differences and 3) discussion of causal and other factors underlying the effects of age, period and cohort. Methods: Cohort analysis was used to study changes in oral health over time. Study participants were selected by random sampling in 1973, 1983, and 1994 (n½1959, n½ 3195, n½2341 respectively).